(3CfS GdLdjS aj Ldh GdMfGOjS Yf SjfjI GHf HGOjSs - (3CMeO Hf eMeO Hf YKeGf Hf jYbhH GdeYQha HGHf GdMGLs; (3GHf HGOjSs
(3ChdgG (B:s
(3GdMeO ddg GdPi CSHZ Ydi ChdjGFg fYeI XGgQI hHGWfI s
(3BNQgG (B:s
(3jGQMef GdOfjG hGdBNQI EQMe YHOkG dGjedc OfjG hdGBNQI KdGKkG s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B148 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B53 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs